Unsupervised home use of an overnight closed‐loop system over 3–4 weeks: a pooled analysis of randomized controlled studies in adults and adolescents with type 1 diabetes. Issue 5 (9th January 2015) - Thabit, H.; Elleri, D.; Leelarathna, L.; Allen, J. M.; Lubina‐Solomon, A.; Stadler, M.; Walkinshaw, E.; Iqbal, A.; Choudhary, P.; Wilinska, M. E.; Barnard, K. D.; Heller, S. R.; et al.
<x xml:space="preserve">Abstract</x> Aims To compare overnight closed‐loop and sensor‐augmented pump therapy in patients with type 1 diabetes by combining data collected during free‐living unsupervised randomized crossover home studies. Methods A total of 40 participants with type 1 diabetes, of whom 24 were adults [mean ± standard deviation (s.d.) age 43 ± 12 years and glycated haemoglobin (HbA1c) 8.0 ± 0.9%] and 16 were adolescents (mean ± s.d. age 15.6 ± 3.6 years and HbA1c 8.1 ± 0.8%), underwent two periods of sensor‐augmented pump therapy in the home setting, in combination with or without an overnight closed‐loop insulin delivery system that uses a model predictive control algorithm to direct insulin delivery. The order of the two interventions was random; each period lasted 4 weeks in adults and 3 weeks in adolescents. The primary outcome was time during which sensor glucose readings were in the target range of 3.9–8.0 mmol/l. Results The proportion of time when sensor glucose was in the target range (3.9–8.0 mmol/l) overnight (between 24:00 and 08:00 hours) was 18.5% greater during closed‐loop insulin delivery than during sensor‐augmented therapy (p < 0.001). Closed‐loop therapy significantly reduced mean overnight glucose levels by 0.9 mmol/l (p < 0.001), with no difference in glycaemic variability, as measured by the standard deviation of sensor glucose. Time spent above the target range was reduced (p = 0.001), as was time spent in hypoglycaemia (<3.9 mmol/l; p = 0.014) during closed‐loop therapy. Lower mean overnight glucose levels during closed‐loop therapy were brought about by increased overnight insulin delivery (p < 0.001) without changes to the total daily delivery (p = 0.84). Conclusion Overnight closed‐loop insulin therapy at home in adults and adolescents with type 1 diabetes is feasible, showing improvements in glucose control and reducing the risk of nocturnal hypoglycaemia.